2008
DOI: 10.1111/j.1365-3024.2008.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the Echinococcus granulosus cyst wall to complement activation: analysis of the role of InsP6 deposits

Abstract: The larva of the cestode Echinococcus granulosus (hydatid cyst) is protected by the acellular laminated layer (LL). The mechanisms that make this thick coat a poor activator of host complement are incompletely understood. The structure binds, through unknown motifs, the host regulator of the alternative complement pathway (ACP), factor H. A second potential mechanism of ACP regulation, the inhibition of factor B activation, was detected in assays employing purified components (Immunopharmacology 42 : 91). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…The issue has been addressed for the complement system, where triggering of this cascade by the LL is much less effective than that by other E. granulosus materials (3, 20, 21). For innate immune cells, two studies focusing on nitric oxide production by macrophages showed that LL-derived materials inhibit this response in cells stimulated with lipopolysaccharide (LPS) or gamma interferon (IFN-γ) (22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…The issue has been addressed for the complement system, where triggering of this cascade by the LL is much less effective than that by other E. granulosus materials (3, 20, 21). For innate immune cells, two studies focusing on nitric oxide production by macrophages showed that LL-derived materials inhibit this response in cells stimulated with lipopolysaccharide (LPS) or gamma interferon (IFN-γ) (22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…We have not observed differences between preparations containing or lacking this component with respect to DC/macrophage responses . The deposits give rise to an enormous surface for protein adsorption, and host proteins that associate with the LL (except for specific antibodies) tend to be adsorbed on this component . These deposits might therefore act as the ‘sticky pad’ for conventional protein antigens, leading to their targeting to liver macrophages, and/or their uptake by DCs that are concomitantly conditioned by LL particles .…”
Section: Molecules Making Up the Llmentioning
confidence: 82%
“…The so‐called alternative pathway of complement activation is controlled on the LL through binding the soluble host regulator factor H . Factor H‐dependent inactivation of the covalently deposited active form of the central component C3 is unaffected by previous extraction of calcium Ins P 6 . This suggests that there are functional sites for factor H on the LL mucins, but the nature of such sites is still unknown.…”
Section: Molecules Making Up the Llmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinococcus granulosus , a cestode that causes cystic echinococcosis in humans, expresses a protein that sequestrates FH on the hydatid cyst wall to inhibit complement C3b deposition (Diaz et al, 1997; Breijo et al, 2008). The binding molecule remained unknown until further research showed that it was InsP6, a major component of the acellular laminated layer (LL) of the hydatid cyst wall, that was bound with FH to inhibit the alternative pathway (Irigoin et al, 2008). Mosquito midgut epithelial cells also express two proteins (40 and 100 kDa) as receptors that captured FH to inhibit the deposition of C3b and impair activation of the alternative complement pathway (Khattab et al, 2015).…”
Section: Complement Evasion By Parasitesmentioning
confidence: 99%